Toxicity Evaluation of Lycopodiaceae Extracts on Mouse Neuronal Cells and Zebrafish Embryos - Kien, Kieu Trung; Trang, Pham Thi Huyen; Thanh, Nguyen Thi Kim; Dat, Nguyen Tien; Thanh, Nguyen Lai; Hanh, Hoang Thi My (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 3, 2021)
Many species in the family Lycopodiaceae possess highly potential medical substances and are widely used as traditional medicines in the treatment of stroke, dementia. Hundreds of Lycopodium alkaloids were described and studied for their biological activities such as anti-inflammatory, antioxidant, immunomodulatory, neuroprotective,… Various members of this family were found in Vietnam and were used as oral traditional medicine for a long time. However, there is a lack of toxicity studies on this subject. In this study, three alkaloid fractions from Huperzia serrata (Thunb.) Trevis, Lycopodium clavatum L. and Huperzia squarrosa (G. Forst.) Trevis were tested in two toxicity models: mouse primary neuronal cell ( in vitro ) and zebrafish ( Danio rerio ) embryos ( in vivo ). The IC 50 values of Huperzia serrata (Thunb.) Trevis, Lycopodium clavatum L. and Huperzia squarrosa (G. Forst.) Trevis on the mouse primary neuronal cells were 0.839, 1.071 and 0.915 mg/ml and on the zebrafish embryo were 0.180, 0.281 and 0.198 mg/ml, respectively. Notably, three common types of maldevelopment: hemostasis, cardiac sac edema and tail defect were recorded; and the teratogenic index of Huperzia serrata (Thunb.) Trevis was 3.418, which indicated high teratogenic effect at embryo developmental stage. These data can be used as a reference in using the alkaloid fractions from these plants in the traditional medicine treatment system, especially when used with high concentration and in treating pregnant women.